Analysis of endocrine autoimmunity by cloning human T lymphocytes from target tissues - Feldmann, M; Londei, M (1987)
Provided certain pitfalls are avoided, the development of T cell lines and clones from the infiltrating tisues of autoimmune diseases provides a powerful approach to describing the mechanism of the diseases in their established chronic form. It remains to be established whether they will provide major clues to their aetiology. T cell clones are capable of providing clues which help design the therapeutic strategies of the future. Thus by determining which lymphokines are present, and their abdundance, it is possible to determine which mediators need to be inhibited. Alternatively, the antigenic specificity of autoreactive T cells may provide the means by which they can be eliminated, either by inducing immunological tolerance with antigen or peptides (Lamb and Feldmann, 1984) or perhaps antigen-coupled toxins. The antigen-specific T cell receptors may provide a target for their elimination or inhibition, provided that the T cells are of restricted clonality which could be determined by studying DNA rearrangements of T cell receptor genes in the T cell clones.